Kilim Karst Geoforest park: the hidden gems of Langkawi under threat - Mansor, Mazlina; Ibrahim, Putri Haryati; Mohd Ismail, Widad (Zes Rokman Resources, 2019)
Tourism is one of the vital contributions to the Malaysian economy. Both tourism and natural resources are significant to the economic growth and human well-being. The tourism activities contribute revenues to the country and inspire humanity to appreciate the natural environment. While, the natural resources contribute to the economy and support the cycle of the natural ecosystem. Nonetheless, the increasing demands for ecotourism and nature-based tourism in recent years have also impacted the natural environment. Globally, air travel and other vehicles meant for traveling, contribute to the increasing causes of greenhouse gas emissions, habitat loss, and degradation of various types of environments, such as coastal areas, mountains, wilderness areas, rural landscape and small islands. The environmental impacts of tourism are also in line with the increasing awareness on environmental issues since 1970’s. It is the combination of creating tourism as a form of economic development and simultaneously brings together conservation issues. This paper presents the uniqueness of Kilim Karst Geoforest Park in Langkawi Island as one of valuable natural heritage assets for Malaysia. It identifies eco-tourism features of the site and the threats of tourism activities using various reviews of literature. The needs of the conservation efforts of the site are vital as UNESCO-certified sites in Southeast Asia. Environmental impacts of tourism have to be explored by all parties that involved in tourism activities. Professionals in the built environment such as Landscape Architects and Planners believe that effective design and management, the existence of “symbiosis” between tourism and the environment is possible to reach. The term “ecotourism”, that was used since the mid-1980s are created to suggest a symbiotic relationship between tourism development and the natural environment. It is not only possible, but perhaps it also the utmost step in balancing tourism and conserving the natural resources. Balancing tourism and resource conservation are essential in due to support the economic growth and to sustain the natural environment. Therefore, knowledge on the effect of tourism activities towards natural resource is imperative in sustaining the environment.